Trans-Aconitic acid-based hetero-Diels-Alder reaction in the synthesis of thiopyrano[2, 3-d][1, 3]thiazole derivatives. Issue 18 (3rd May 2017) - Zelisko, Nataliya; Karpenko, Olexandr; Muzychenko, Volodymyr; Gzella, Andrzej; Grellier, Philippe; Lesyk, Roman
Graphical abstract: Highlights: trans -Aconitic acid was used for the synthesis of thiopyrano[2, 3- d ]thiazoles synthesis. One-pot, three-component method for the synthesis of spiro-pyrrolidinedione-thiopyrano[2, 3- d ]thiazoles. Regio- and stereoselectivity of the hetero -Diels-Alder reaction was discussed. Compound4e possesses trypanocide activity against Trypanosoma brucei . Abstract: The hetero -Diels-Alder reaction of 5-arylideneisorhodanines with trans -aconitic acid proceeds as a regio- and diastereoselective process with spontaneous decarboxylation of the [4+2]-adduct to furnish thiopyrano[2, 3- d ][1, 3]thiazole (2 ) and chromeno[4′, 3′:4, 5]thiopyrano[2, 3- d ]thiazole (3 ) derivatives analogously to the use of itaconic acid as a dienophile. Conversely, the one-pot, three-component reaction of 5-arylideneisorhodanines, trans -aconitic acid and anilines proceeded without decarboxylation, leading to novel rel -(5′ R, 6′ R, 7′ R )-5′-carboxy-7′-aryl-1-aryl-3′, 7′-dihydro-2 H, 2 ′ H, 5 H -spiro[pyrrolidin-3, 6′-thiopyrano[2, 3- d ]thiazol]-2, 2′, 5-triones4 . Interestingly, the use of trans -aconitic acid trimethyl ester led to the opposite regioselectivity, yielding rel -(5 R, 6 S, 7 S )-5-methyloxycarbonylmethyl-2-oxo-7-aryl-3, 5, 6, 7-tetrahydro-2 H -thiopyrano[2, 3- d ]thiazol-5, 6-dicarboxylates5 . Selected compounds were examined for trypanocide activity against the bloodstream forms of Trypanosoma brucei where compound4e showed the highest activity (IC50 = 6.74 μM).